A METHODOLOGY FOR DEVELOPING STUDENTS’ PROFESSIONAL COMPETENCE BASED ON THESAURUS TECHNOLOGY - Abdullayeva , Nigora (QO‘QON UNIVERSITETI XABARNOMASI, 2025)
This study presents a comprehensive methodology for developing students’ professional competence through the systematic application of thesaurus technology in higher education contexts. Professional competence, understood as the integration of knowledge, skills, and attitudes necessary for effective professional practice, requires structured pedagogical approaches that facilitate terminological precision, conceptual understanding, and domain-specific communication abilities. Thesaurus technology, encompassing both traditional lexicographic resources and modern computational tools, offers a robust framework for organizing disciplinary knowledge and enhancing students’ mastery of professional discourse. This article examines the theoretical foundations of competence-based education and thesaurus applications, proposes a structured methodology incorporating thesaurus technology into curriculum design and instructional practice, describes implementation procedures across various educational settings, and discusses the implications for professional education. The proposed methodology integrates thesaurus construction activities, controlled vocabulary exercises, and semantic network analysis to develop students’ terminological competence, conceptual mapping abilities, and professional communication skills. Findings from preliminary applications suggest that thesaurus-based approaches significantly enhance students’ understanding of disciplinary knowledge structures, improve their precision in professional discourse, and facilitate the development of critical thinking skills essential for professional practice. The article concludes with recommendations for educators seeking to implement thesaurus technology in competence development programs and identifies directions for future research in this emerging pedagogical domain.